Raven tales. Spiders and dreams [videorecording (DVD)] (Indigenous Collection., 2017)
When Dza's nightmares leave her scared and confused, Wina says he'll watch over her while she sleeps, but, when he falls asleep, too, he meets Spider in the dream world.